Industrial Transformation of Kazakhstan in Digitalization’s Era - AGUMBAYEVA, A. Ye.; CHMYSHENKO, E. Gr.; PULYAEV, N. N.; BUNKOVSKY, D. V.; KOLESOV, K. I.; AMIROVA, E. F. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
This investigation traces the differences of terms as ‘informatization and ‘digitalization’ and the role both of them for industry process. This investigation explores the ways of thinking of term of ‘digitalization’ for improving the life circle of product and how this process could be harmful without control of special technologies. In this paper was used different points of view of scientists as Atkins (2016), Quinton (2013), Istomina (2018), Plotnikov (2018), Khalin and Chernova (2018) and others. This paper describes the conditions of experience in informatization and digitalization processes in the world and in countries of CIS. According to famous rating Kazakhstan ranks 52 nd among 176 countries of the world and in the CIS region Kazakhstan is among the top three, occupying the 3rd place after Belarus (32 nd place) and Russia (45 th place). As the methodological base of the study, we such principles of cognition of economic phenomena as dialectical and systemic, which allowed us to consider the phenomenon under study and processes in development. At the same time, in this paper we used traditional techniques such as analysis and synthesis. This investigation has its aim to illustrate the main perspectives after using of big data in industrial sphere especially in mining industry as one of the leading one in Kazakhstan .